Learner, Lecturer and School Factors as Predictors of Achievement in Mathematics in Colleges of Education in Southwestern Nigeria (2016)
Mathematics is a core subject in schools and a bedrock for scientific and technological development. To this end, qualified teachers must be produced at colleges of education (CoEs) in Southwestern Nigeria to teach the subject at basic education level. In recent times, the performance of learners of Mathematics in the CoEs in Southwestern Nigeria has not been encouraging. Most studies focused on instructional strategies for teaching Mathematics to the neglect of influencing factors. This study, therefore, investigated learners’ attitude towards Mathematics, peer influence, self-efficacy in Mathematics, attitude to Mathematics teaching, perception to teaching, teaching experience, availability of infrastructure, textual materials and instructional materials as predictors of learners’ achievement in Mathematics in CoEs in Southwestern Nigeria. The study adopted the survey design of the correlational type while Vygotsky’s social learning and environmental learning theories provided the framework. Five CoEs from Southwestern Nigeria: three owned by states (Ikere Ekiti, Ijanikin and Ila-Orangun) and two owned by the Federal government (Ondo and Oyo) were purposively selected based on the high number of Mathematics lecturers. Total enumeration was used to draw 511 final year pre-service Mathematics teachers made up of 211 males and 300 females whose age falls within the range of 18 and 32 and 51 Mathematics lecturers in the five colleges. The instruments used for data collection were: Mathematics Achievement Test (r = 0.75), Learner’s Attitudes to Mathematics (r = 0.74) and Lecturer’s Attitude towards Mathematics Teaching (r = 0.79). Others were Learners’ Mathematics Self-Efficacy (r = 0.93), Learner’s Peer Influence (r = 0.92) scales, Teaching Experience, Availability of Infrastructure, Instructional and Textual Material checklists and Mathematics Lecturers’ Perception to Teaching Rating Scale (r = 0.77). Data were analysed using descriptive statistics and Multiple Regression Analysis at 0.05 level of significance. Learners’ average performance in Mathematics achievement test was 19.55%. There was significant joint contribution of lecturer variables on learners’ achievement in Mathematics (F(3,47) = 3.87; R = 0.44) accounting for 14.7% of its variance. Teachers’ experience (B=0.39,t=2.66) and perception to teaching (B = 0.35, t = 2.43) predicted learners’ achievement in Mathematics. There was significant joint contribution of the school variables on learners’ achievement in Mathematics (F(3, 507) = 6.66; R = 0.20) accounting for 3.2% of its variance. Instructional (B = 0.18, t = 3.31) and textual (B = 0.13, t = 2.58) materials predicted pre-service teachers’ achievement in Mathematics. None of the learner variables predicted learners’ achievement in Mathematics. There was significant joint contribution of the nine variables on achievement in Mathematics (F(9, 501) =16.67; R=0.48). This accounted for 21.7% of the total variance when the nine predictor variables are taken together. Lecturer’s teaching experience, positive perception of teaching, relevant instructional and textual materials were determinants of learner’s achievement in Mathematics in colleges of education in Southwestern Nigeria. Education policy makers and management of these colleges should take cognisance of these factors for improved learning outcomes in the subject.